Non-AIDS-defining comorbidities impact health related quality of life among older adults living with HIV - Zhabokritsky, Alice; Klein, Marina; Loutfy, Mona; Guaraldi, Giovanni; Andany, Nisha; Guillemi, Silvia; Falutz, Julian; Arbess, Gordon; Tan, Darrell H. S.; Walmsley, Sharon (Frontiers in Medicine, 2024)
Introduction The life expectancy of people living with HIV receiving effective combination antiretroviral therapy is approaching that of the general population and non AIDS-defining age-related comorbidities are becoming of greater concern. In order to support healthy aging of this population, we set out to explore the association between multimorbidity (defined as presence of 2 or more non AIDS-defining comorbidities) and quality of life (QoL). Methods We performed a cross-sectional analysis using data from the Correlates of Healthy Aging in Geriatric HIV (CHANGE HIV) study, a Canadian cohort of people living with HIV age 65 years and older. Study participants completed two QoL modules, the general QoL and health related QoL (HR-QoL). Results 433 participants were included in the analysis with a median age of 69 years (interquartile range, IQR 67–72). The median number of comorbidities among study participants was 3 (IQR 2–4), with 78% meeting the definition of multimorbidity. General QoL scores (median 66, IQR 58–76) were lower than HR-QoL scores (median 71, IQR 61–83) and were not associated with multimorbidity after adjusting for age, sex, relationship status, household income, exercise, tobacco smoking history, malnutrition, time since HIV diagnosis, and HIV-related stigma. In contrast, multimorbidity was associated with lower HR-QoL (adjusted β = −4.57, 95% CI −8.86, −0.28) after accounting for the same variables. Several social vulnerabilities (not having a partner, low household income), health behaviours (lower engagement in exercise, smoking), and HIV-related factors (HIV stigma, longer time since HIV diagnosis) were also associated with lower QoL. Discussion Overall, our study demonstrated a high burden of multimorbidity among older adults living with HIV in Canada, which has a negative impact on HR-QoL. Interventions aimed at preventing and managing non-AIDS-defining comorbidities should be assessed in people living with HIV to determine whether this can improve their HR-QoL.